Regulating grain growth and sintering mechanism of Si3N4 ceramics: Three effects achieved simultaneously by controlling the amount of CaF2 additive; Journal of the European Ceramic Society; Vol. 46, iss. 9 - Wei Ning; Xinxin Cao; Guifang Han; Kashkarov E. B. Egor Borisovich; Travitsky (Travitzky) N. Nakhum (2026, 2026)
Title screen